New Silver Nanosensor for Nickel Traces: Synthesis, Characterization and Analytical Parameters - Talio, María Carolina (2011)
A new fluorescence silver nanosensor assisted by surfactant has been synthesized and applied to ultra trace nickel determination. Operational variables which influence nanomaterial synthesis have been studied and optimized. Synthesis was very fast and simple using non polluting solvents; silver chemical reduction was carried out at room temperature. Spectroscopic studies were carried out in order to assure the uniformed of nanomaterial obtained. Fluorescent signal of silver nanoparticles resulted enhanced in presence of Ni(II). At optimal experimental conditions, a detection limit of 0.036 pg·L-1 and quantification limit 0.12 pg·L-1 were obtained. The calibration sensitivity was 2 × 1014 L·pg-1·cm-1 for the new methodology, with a range of linearity of six orders of magnitude between 0.12 and 2.93 × 105 pg·L-1. The tolerance levels for potential interferent ions were studied with good results. The proposed methodology represents a promising approach for Ni(II) traces quantification due to its low operation cost, simplicity of instrumentation, high sampling speed and non-polluting solvents.